Vital role of chest CT in diagnosis of coronavirus disease 2019 (COVID-19) - Zeinab Mohseni Afshar; Soheil Ebrahimpour; Mostafa Javanian; VeneelaKrishna Rekha Vasigala; jila Masrour-Roudsari; Arefeh Babazadeh (Babol University of Medical Sciences, 2020)
In December 2019, a new virus called coronavirus disease 2019 (COVID-19) causing severe acute respiratory syndrome emerged in Wuhan, China, and rapidly spread to other areas of China and other regions of the world. Since it was a discovery, COVID-19 has spread to several countries and to this date, affecting about 2,329,651 people and caused about 160,721 deaths. Since most COVID-19 infected cases were diagnosed with pneumonia and characteristic chest computed tomography (CT) scan patterns, radiological examinations have become an important tool in early diagnosis. Nowadays, CT findings combined with normal blood cells (WBCs), lymphopenia and a history of epidemiological exposure have been used as criteria for clinical diagnosis of COVID-19. It is noteworthy that reverse transcription polymerase chain reaction (RT-PCR) test is still gold standard for the diagnosis. This review focuses on role of chest CT in the clinical evaluation of disease progression and more accurate diagnosis.